(untitled) (Innovative professional education, 2024)
International projects implemented in Khmelnytskyi Centre for VET of Service Sector. It is noted that as a result of the project activity, the quality of services increases, the needs of consumers of educational services are met, and the competitiveness of the educational institution is maintaine